2011
DOI: 10.1111/j.1440-172x.2011.01957.x
|View full text |Cite
|
Sign up to set email alerts
|

Hand-washing behaviour and nurses' knowledge after a training programme

Abstract: The aim of this study was to evaluate the nurses' hand-washing behaviour and knowledge before and after a training programme. This prospective study involved 200 nurses who participated in hand-washing training at a university hospital in Turkey. The data were collected using a personal information form and pre- and post-test surveys that had been developed by the researchers. During the study, the nurses received 40 min of training on hand washing and a handbook prepared by the researchers. The hand-washing b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 28 publications
0
8
0
3
Order By: Relevance
“…Several studies have provided evidence that health worker hand hygiene practices greatly improve when interventions are implemented after baseline surveys [5,6,26]. Providing a planned HH training programme to health workers is important in creating sensitivity and renewing knowledge on the subject [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have provided evidence that health worker hand hygiene practices greatly improve when interventions are implemented after baseline surveys [5,6,26]. Providing a planned HH training programme to health workers is important in creating sensitivity and renewing knowledge on the subject [26].…”
Section: Discussionmentioning
confidence: 99%
“…Providing a planned HH training programme to health workers is important in creating sensitivity and renewing knowledge on the subject [26]. A 2011 survey by Erkan et al in which the HH behaviour and knowledge of nurses were evaluated before and after training, determined that training increased the nurses' knowledge of HH, the frequency and time the nurses spent practicing HH, and the quality of HH practiced by the nurses [26].…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to these results, one of the analyzed studies (10) found that adherence was higher among nurses (50%) than among doctors (45%) and other health professionals (38.4%). Only one of the included studies focused on a single professional group: nurses (7) . It should be noted that adherence to hand hygiene was higher among trained professionals than among untrained ones (76% versus 63%; p<0.005), and that antiseptic solutions were used when hand washing was not possible (9) .…”
Section: Discussionmentioning
confidence: 99%
“…According to the authors of the studies included in this review, health professionals' training has a direct impact on the adherence to hand hygiene (6)(7)(8)(9)(10) . Therefore, these studies have contributed to answering the research question.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation